Tunicamycin inhibits cell proliferation and migration in hepatocellular carcinoma through suppression of CD44s and the ERK1/2 pathway. Issue 4 (26th February 2018) - Hou, Helei; Ge, Chao; Sun, Hefen; Li, Hong; Li, Jinjun; Tian, Hua
Abstract : Tunicamycin (TM) is an N ‐linked glycosylation (NLG) inhibitor with strong antitumor activity, the exact underlying molecular mechanism of which remains to be elucidated. In our previous studies, we found that TM reversed drug resistance and improved the efficacy of combination treatments for hepatocellular carcinomas (HCC). Here, we investigated the effects of TM on HCC cell proliferation and migration as well as the mechanism of those effects. Our results showed that TM inhibited cell proliferation and migration as well as induced apoptosis of hepatocellular carcinoma cells. TM inhibited proliferation of HCC cells by inducing cell apoptosis and cell cycle arrest at the G2/M phase. Meanwhile, TM inhibited migration of HCC cells by suppressing CD44s‐mediated epithelial‐mesenchymal transition (EMT). TM inhibited migration and invasion of HCC cells by decreasing CD44 expression and altering its glycosylation. In addition, CD44s is involved in promoting EMT and is associated with a poor prognosis in HCC patients. Overexpression of CD44s promoted tumor migration and activated phosphorylation of ERK1/2 in HCC cells, whereas TM inhibited CD44s overexpression‐associated cell migration. The ability of TM to inhibit cell migration and invasion was enhanced or reversed in CD44s knockdown cells and cells overexpressing CD44s, respectively. The MEK/ERK inhibitor U0126 and TM inhibited hyaluronic acid‐induced cell migration in HCC cells. Furthermore, TM inhibited exogenous transforming growth factor beta (TGF‐β)‐mediated EMT by an ERK1/2‐dependent mechanism and restored the TGF‐β‐mediated loss of E‐cadherin. In summary, our study provides evidence that TM inhibits proliferation and migration of HCC cells through inhibition of CD44s and the ERK1/2 signaling pathway. Abstract : Our study provides evidence that tunicamycin inhibited HCC cell proliferation and migration through inhibition of the CD44s and ERK1/2 signaling pathway.